2018
DOI: 10.1038/s41598-018-33619-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive continuous real-time in vivo analysis of microbial hydrogen production shows adaptation to fermentable carbohydrates in mice

Abstract: Real time in vivo methods are needed to better understand the interplay between diet and the gastrointestinal microbiota. Therefore, a rodent indirect calorimetry system was equipped with hydrogen (H2) and methane (CH4) sensors. H2 production was readily detected in C57BL/6J mice and followed a circadian rhythm. H2 production was increased within 12 hours after first exposure to a lowly-digestible starch diet (LDD) compared to a highly-digestible starch diet (HDD). Marked differences were observed in the faeca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 77 publications
3
39
0
Order By: Relevance
“…The human fecal samples were collected at home by the participants and stored at 4 • C. Within 24 hours after collection, the samples were transported to the laboratory, aliquoted into 1.5 ml Eppendorf tubes, and stored at -80 • C. The bacterial DNA was extracted using a repeated bead-beating step and the Maxwell®16 Instrument (Promega, Leiden, The Netherlands), as described previously [21]. DNA purification was performed with a customized kit (AS1220; Promega, Leiden, The Netherlands).…”
Section: Sample Collection Preparation and Sequencingmentioning
confidence: 99%
“…The human fecal samples were collected at home by the participants and stored at 4 • C. Within 24 hours after collection, the samples were transported to the laboratory, aliquoted into 1.5 ml Eppendorf tubes, and stored at -80 • C. The bacterial DNA was extracted using a repeated bead-beating step and the Maxwell®16 Instrument (Promega, Leiden, The Netherlands), as described previously [21]. DNA purification was performed with a customized kit (AS1220; Promega, Leiden, The Netherlands).…”
Section: Sample Collection Preparation and Sequencingmentioning
confidence: 99%
“…Sample collection, preparation and sequencing:The human fecal samples were collected at home by the participants and stored at 4 o C. Within 24 hours after collection, the samples were transported to the laboratory, aliquoted into 1.5 ml Eppendorf tubes and stored at -80 o C. The bacterial DNA was extracted using a repeated bead-beating step and theMaxwell® 16 Instrument (Promega, Leiden, The Netherlands), as described previously[21]. DNA purification was performed with a customized kit (AS1220; Promega).…”
mentioning
confidence: 99%
“…All of the experimental diets were based on the BIOCLAIMS standard diet [ 25 ]. Both HDD and LDD contained 20 energy percentage (en%) protein, 55 en% carbohydrates, and 25 en% fat, with highly-digestible or lowly-digestible starches as the sole difference and source of available carbohydrate (Cargill, Sas van Gent, The Netherlands; incorporated into pelleted diets by Research Diet Services), as published [ 9 ]. The HFD contained 20 en% protein, 40 en% carbohydrates, and 40 en% fat [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Using highly defined diets, with only the type of starch being different, we have previously shown that a low versus high GI diet delayed obesity-associated disease development in adult mice [ 8 ]. Moreover, the low versus high GI diet induced intestinal microbiota hydrogen production in young and adult mice [ 9 ]. Thus, the digestibility of starches provides them with different nutritional properties for both the host and the intestinal microbiota through fermentation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%